GENDER DIVERSITY IN TOP MANAGEMENT TEAMS AND ITS EFFECTS ON NATIONAL COMMERCIAL BANKS' PERFORMANCE - Zaenal ABIDIN (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
This study intends to investigate how the performance of the national commercial banks BUKU 1 and BUKU 2 is impacted by the gender diversity of the Top Management Team. This study uses quantitative methods to determine the link between the investigated variables. The Partial Least Square (PLS) method, which uses SmartPLS software, is the methodology used in this study. Using a purposive sampling technique, 30 banks were included in the sample. The study's data came from the bank's annual report from 2018 to 2019. The findings of this study demonstrated that gender diversity could be considered in the selection of the top management of BUKU 1 and BUKU 2 banks since it significantly affects the Net Interest Margin. However, non-performing loans, BOPO ratio, and corporate profitability are not significantly impacted by gender diversity. At the same time, neither NPL nor NIM significantly affecting ROA. Nevertheless, BOPO ratio has a significant impact on ROA. This study contributes to enriching research of gender Top Management Team and its contribution on performance bank in Indonesia. This study will outline the connection between TMT gender diversity and business performance, allowing businesses to take that into account when assembling their top management teams (TMT).